Chinese students’ motivation for learning German and French in an intensive non-degree programme - Chen, Yu; Zhao, Dan; Qi, Shen (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This paper reports on a mixed method study that examined the motivation of 121 students in a 1-year intensive language course in German or French at a Chinese university. Drawing on Dörnyei’s (2009) theory of the L2 Motivational Self System (L2MSS), a survey was conducted to explore their motivation to learn German or French. Regression analyses revealed that learning experience and promotion-focused instrumentality were the predictors for the German learners’ intended learning effort, while ideal L2 self was the predictor for the French learners’ motivation. Furthermore, ought-to self, culture/community interest and prevention-focused instrumentality were excluded in both regression models. In addition, 17 participants’ qualitative data in the interviews suggested that most of them had lower expectations for the value of German or French than for the value of English in improving one’s employability. Instead, they were much more oriented to learn and appreciate the cultural values of these languages. The results provided insight into the complexity of motivation to learn Languages Other than English (LOTEs) in the university context in China, and suggested future direction for research on LOTE learning motivation
Keywords: Motivation; German learning; French learning; China; L2MSS